THUNDERBOOTS - Jones, Naomi; Ashdown, Rebecca (Oxford : Oxford University Press, 2023)
Trixie is the LOUDEST (and the littlest) person in Primrose Tower. Her neighbours love her fizzy energy. 'Here comes Thunderboots!' they say. But when Trixie starts school everything is NEW and everything feels HARD. Trixie begins to lose her sparkle. Can Dad, Miss Fry, and her friends make things easier for Trixie so thar she can get back the spring in her step...
Keywords: English language -- Readers; Children's stories, English; Dyslexia -- Juvenile fiction